ANALYSIS OF ERP SYSTEM IMPLEMENTATION AND SUPPLY CHAIN IN PT INDOFOOD CBP SUKSES MAKMUR - Cuandra, Fendy; Rudiyanto; Junita; Theo, Stella; Ardiansyah, Rano; Tjoa, Kevin; Darvin; Jessy (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
PT Indofood Sukses Makmur is a company engaged in the food sector. The impact of the pandemic was very influential, causing a decrease in the purchasing power of products from suppliers to distributors and the global crisis caused by this pandemic caused a shift in consumer spending tendencies from those that tended to be evenly distributed between main needs. This study aims to analyze the ERP system implementation and supply chain in PT Indofood CBP Sukses Makmur. In managing information on the company, PT Indofood CBP Sukses Makmur Tbk. Implementing an Enterprise Resource Planning or ERP system as an integration system for the company's business functions. The implementation of the ERP system at PT Indofood CBP Sukses Makmur can be considered a success if the implementation of this system can integrate work functions and reduce the need for manual work.